INJIL, BUDAYA DAN PANCASILA BAGI TRANSFORMASI SOSIAL MENURUT KAJIAN RICHARD SIWU SEBAGAI GAGASAN TEOLOGI PUBLIK INDONESIA - Marde Christian Stenly Mawikere; Sudiria Hura; Jean Calvin Riedel Mawikere (DA'AT : Jurnal Teologi Kristen, 2024)
This article examines the role of the Gospel, Minahasan culture, and Pancasila in Indonesia's social transformation, using Richard Siwu's contributions as a primary framework. The introduction highlights the relevance of these three elements in the context of societal modernization, particularly in Minahasa, Indonesia. Richard Siwu, through his integrated approach of theology, cultural studies, and sociology, depicts the complexity of interaction and mutual influence among Christianity, Minahasan indigenous traditions, and the national ideology of Pancasila. The research methodology employs a qualitative approach with content analysis to delve into the complex concepts within Siwu's works and other relevant literature. Findings indicate that integrating Christian values, local culture, and Pancasila principles has the potential to strengthen an inclusive national identity and promote positive social change in Indonesia. The conclusion emphasizes the analytical outcomes on how the interaction of these three elements can support social harmony and sustainable national development. Thus, this article contributes significantly to understanding the complex dynamics of religion, culture, and politics in Indonesia and their implications for future modern and inclusive development. Keywords: Gospel, Religion, Culture, Pancasila, Social Transformation